Profiling immune markers for identification of leukocytes in brown-marbled grouper Epinephelus fuscoguttatus (Forsskal, 1775) - Chong, Chou Min (2014)
The high market value of grouper has encouraged a greater impetus for its development in aquaculture. Rapid expansion of mariculture of grouper however has been hampered by serious outbreaks of infectious diseases in the industry which poses a pressing need for disease prevention programs and supportive input from immunological studies on this premium fish. However, fundamental difficulties such as rapid blood clotting during blood collection,unsuitability of standard reagents for isolating leukocytes and paucity in monoclonal antibody (MAb) markers for identifying leukocyte subsets has hindered the progress of immunological studies in this field. The general aim of this study was to develop methodologies to isolate and identify leukocyte subpopulations in grouper. Various methodologies were used. Experimentation with different combinations of anticoagulants identified a new preparation which effectively prevented the remarkably rapid blood clotting capabilities of grouper (Epinephelus fuscoguttatus). This anticoagulant also prevented the blood coagulation in other tropical fish. Isopycnic density gradient showed that all of the grouper peripheral leukocytes possess heterogeneous densities and were hardly able to be purified using this method. Cytological assessment via microscopic observations of Romanowsky stained grouper blood cells revealed the five major cell components present, namely lymphocyte, thrombocyte, erythrocyte, monocyte, and granulocyte. Cytochemical stainings were also useful to characterise these cells. Putt’s Eosin staining was found to differentiate grouper leukocytes into five clusters in flow cytometry and each was shown to correlate significantly with the aforementioned main cell types. Distinct flow cytometric light scattering characteristics of these subsets with eosin mirrored the biophysics of the cells in microscopic studies. The utilisation of flow cytometric eosin profile in cell subset identification is novel and applicable on other fish species. The profile was used to indicate granulocyte: lymphocyte ratio, whereby the index reflects inflammation status in fish groups treated with Vibrio parahaemolyticus relative to the control group. A panel of MAbs was developed against various blood cells of E. fuscoguttatus using the hybridoma fusion technique. Four (EF118, EF124, EF353 and EF512) were further characterised. With a combination of immunochemistry assessments, flow cytometric analyses, and mitogeninduced leukocyte proliferation assays. EF118 was identified as a general marker for grouper lymphocytes, EF512 was identified a subset of lymphocyte, EF124 appeared to be specific for monocytes/macrophages, while EF353 stained mature blood cells (haematocytes). These markers were also used to profile changes in cellular compositions in grouper blood and spleen of controls and 4 hours acute infection with V. parahaemolyticus. Results showed modulation in percentage of EF118 and EF124 positive cells in these tissue/organ. Immunopanning with the EF118 monoclonal antibody was also tested to iso ate specific cells from peripheral blood of grouper and successfully purified more than 95% of lymphocyte. With the successfully establishment of the methodologies and reagents in isolation and characterisation of leukocytes subsets in grouper blood and lymphoid organs,in addition to the development of MAB and non-MAb markers, immune responses of the grouper could be monitored against various environmental or biotic stressors and immunoprophylactic treatments that will lead to improvement of programs in aquaculture of brown-marbled grouper.